Analysis of the Existence of Political Parties as Pillars of Democracy in Legislative Elections in Indonesia - Afrizal Afrizal; Tamaulina Br. Sembiring; Ali Yusran Gea (Utan Kayu Publishing, 2025)
Political parties are a key instrument in the modern democratic system, serving as a means of articulating and aggregating the people's interests. Their existence plays a vital role in determining the quality of democracy, particularly in the implementation of legislative elections in Indonesia. This study aims to analyze the existence of political parties as pillars of democracy in the context of legislative elections, by reviewing their roles, functions, and the challenges faced in strengthening political representation of the community. The method used is normative research with a legislative, conceptual, and historical approach, complemented by an analysis of academic literature and related regulations. The results of the study indicate that although political parties have been constitutionally recognized as the main pillars of democracy, their implementation still faces various problems, such as weak internal party democratization, oligarchic practices, money politics, and a crisis of popular representation. This has resulted in declining public trust in political parties. Therefore, strengthening regulations, internal party reform, and increasing public political participation are necessary so that political parties can optimally carry out their functions as pillars of democracy. This research is expected to contribute to the development of constitutional law and politics, as well as serve as a reference in the formulation of election policies in Indonesia.